THE EFFECT OF COMPLIANCE WITH THE INDONESIAN VALUATION CODE OF ETHICS AND THE IMPLEMENTATION OF INDONESIAN VALUATION STANDARDS ON VALUATION QUALITY MEDIATED BY THE INTENSITY OF VALUERS’ EDUCATION IN INDONESIA - Susanto Hadi, Risal; Siahaan, Elisabet; Mulyadi, Edih (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the effect of compliance with the Indonesian Appraisers’ Code of Ethics (KEPI) and the implementation of Indonesian Valuation Standards (SPI) on valuation quality, with appraisers’ educational intensity serving as a mediating variable among public appraisers in Indonesia. The study employed a quantitative approach using explanatory research. The research population consisted of 845 public appraisers registered with the Center for Financial Profession Development (PPPK). The sampling technique used proportional random sampling, resulting in 100 respondents. Data were collected through online questionnaires using a Likert scale and analyzed using path analysis and the Sobel test. The results indicate that compliance with the Indonesian Appraisers’ Code of Ethics has a positive and significant effect on appraisers’ educational intensity and valuation quality. The implementation of Indonesian Valuation Standards also has a positive and significant effect on appraisers’ educational intensity and valuation quality. In addition, appraisers’ educational intensity has a positive and significant effect on valuation quality. The mediation test results reveal that appraisers’ educational intensity significantly mediates the relationship between compliance with the Indonesian Appraisers’ Code of Ethics and valuation quality, as well as the relationship between the implementation of Indonesian Valuation Standards and valuation quality. This study demonstrates that improving valuation quality is influenced not only by ethical compliance and the implementation of valuation standards directly, but also through strengthening professional competence via continuing professional education. Therefore, professional organizations and related institutions should strengthen ethical enforcement, implementation of valuation standards, and participation in continuing professional education programs to improve valuation quality in Indonesia.